БИОТЕХНОЛОГИЯ ПРОИЗВОДСТВА БИОГАЗА ИЗ ТБО КАРАСАЙСКОГО ПОЛИГОНА (Experimental biology, 2009)
Accelerated process of biodegradation of MSW in bioreactors past 209 days. According to studies we have determined that the process of methanogenesis begins with a pH equal to 7.5. Intensive emission of biogas was observed for 30 days.
Keywords: biodegradation; Intensive emission